COLIBACILLOSIS IN BURAS CHICKENS IN SOUTH KALIMANTAN (KOLIBASILOSIS PADA AYAM BURAS DI KALIMANTAN SELATAN) - Bambang Nganji Utomo (Jurnal Sain Veteriner, 1996)
Thirty eight buras chickens of various ages with clinical signs diseases of illness were diagnosed for colibacillosis and other diseases, The diagnoses were carried out by isolation and identification of causative agents, pathological and histopathological examination. The isolated E. coli were tested serologically and their sensitivity towards antibiotics and sulfouamid.The results indicated that E. coli were isolated from 42.11 % chickens, either as single infection or in the connection with Newcastle Disease, salmonellosis, coccidiosis, aspergillosis, pasteurellosis aad mycoplasmosis. Serological test indicated that 25% of E. coli isolates belong to serotype 0,2 : KI and 18.75% serotype 078 : K80. The Sensitivity test showed that 73.33% of E. coli isolates were resistant to the antibiotics and sulfonamid, where as 26.67% were sensitive.